2009
DOI: 10.1007/s10334-009-0182-2
|View full text |Cite
|
Sign up to set email alerts
|

A digital receiver with fast frequency- and gain-switching capabilities for MRI systems

Abstract: The results show that the phase coherence between the transmitter and the receiver and the dynamic range of the receiver are greatly improved. Consequently, the proposed digital receiver may be useful for obtaining multiple-slice two-dimensional magnetic resonance images with very high resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The Direct Digital RF receiver technology digitizes the MR signal at the patient, and the fiber-optic connection from the coil to the image reconstructor enables lossless broadband data transmission. Previous reports suggested that this technique improved the dynamic range of the RF receiver and resulted in an improved signal-to-noise ratio (SNR) (Ruipeng et al 2009 ). Dual-source radiofrequency transmission with patient-adaptive local radiofrequency shimming enables uniform RF shimming for cardiac MRI (Mueller et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Direct Digital RF receiver technology digitizes the MR signal at the patient, and the fiber-optic connection from the coil to the image reconstructor enables lossless broadband data transmission. Previous reports suggested that this technique improved the dynamic range of the RF receiver and resulted in an improved signal-to-noise ratio (SNR) (Ruipeng et al 2009 ). Dual-source radiofrequency transmission with patient-adaptive local radiofrequency shimming enables uniform RF shimming for cardiac MRI (Mueller et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19] However, most of these focus on either the transmitter 11,16 or the receiver 9,14,15,19 only. Other spectrometers can only be used in ultra-low magnetic fields, 13 or rely on external mixers for down-converting the signals to lower intermediate frequencies.…”
Section: Introductionmentioning
confidence: 99%